A implantação da coleta seletiva de lixo em escolas do município de Araguari (MG): equívocos e perspectivas - Mirna Gertrudes Ribeiro Oliveira (Revista Sociedade & Natureza, 2005)
Human beings have never removed so much of the environment as in recent years. Guided byvalues based on consumerism, they have entered in the dynamics of nature. Removing from it at anycost, its resources: minerals, flora, fauna, besides water, soil and which become more and more aplace of discharge of various pollutants. As a result of this society of consumerism, waste appearsas na ally, producing thousands of tons of garbage daily by human beings. Recently, the politics ofthe administration of urban solid residues in Brazil created by the Federal Government, whichincludes the support of organizations of collectors of recycled waste, has encouraged the implanta-tion of the selective collection of garbage and the passing on of funds for the implantation of sanitary landfills in municipal districts. In Araguari (MG) this process began in 2001. This was themoment in which we participated more directly in the implantation of the selective collection. A lotof experience was accumulated during this participation, especially the implantation of the selec-tive colletion in schools of the municipal district. In this article, we will make reference to theseexperiences, contemplating the misunderstandings and the progress conquered. With this, webelieved to be contributing with those who want, in the school context, to begin or to reformulateways in the universe of the separation of materials be sent to recycling industries.